Cross-border venture capital investments : Why do venture capital firms invest at a distance? - Tarrade, Hortense (Gabler Verlag, 2012)
Hortense Tarrade analyses over 200,000 venture capital (VC) investments over the past 20 years to understand the investors' motivation to select national or foreign companies into their portfolio. She compares the sensitivity of US-based, non-US and German VC firms to the availability of local deal supply and demand as well as the relative importance of their intrinsic capabilities in their investment scope decision ("Why do VC firms invest on a national, continental or global scope?"). Further, she provides an in-depth analysis of the role of geographic and cultural distance in investments by German VCs ("Why do VC firms invest in a target location rather than another?").